Jovens de origens populares no ensino superior: experiências universitárias e projetos de futuro entre estudantes da rede pública - Macedo, Ricardo Cruz (2021)
This thesis is part of the field of sociology on an individual scale. We start from the understanding that Brazilian higher education has undergone, in this current century, changes in the profile of university students with the entry of young people who were previously excluded from academic life. From this, we analyze how university experiences are built and how they influence the redefinition of the future project of young people from popular origins. The campus of the Federal University of Cariri - UFCA, in Juazeiro do Norte-CE, was the locus of the research. The subjects participating in the study were young people from families classified in vulnerable socioeconomic conditions, in accordance with student assistance policies. The data were prepared through semi-structured interviews, carried out during the first half of 2019, with eighteen young people enrolled in different periods of the nine undergraduate courses offered on that campus until the year 2018. We also used questionnaires applied to selected respondents, and quantitative data made available by the Dean of Undergraduate Studies (PROGRAD/UFCA), as well as data from the National Institute of Studies and Research (INEP). From the analyzes carried out, the following considerations were possible: The growth of higher education in Brazil, from the final decades of the 20th century, occurred largely through the private network. However, the advances observed in the first decade of the 21st century, in the public network, brought new contours to the student profiles, expanding the scope of the university experience among the different social segments; In living this experience, the family exerts an important influence on financial and, above all, moral and affective support; The experiences of young people as university students are woven from a set of relationships mediated by academic life that ranges from changes in contacts with the family, university daily life, shared housing spaces, comings and goings to campuses in transport. collectives and spaces of sociability; In host cities, such as Juazeiro do Norte, the growth of higher education brings changes in urban flows and dynamics, which come to live, on a daily basis, with a student population that uses, for example, transport lines, leisure and consumption spaces, or apartment for rent, etc.; Among young people, the acquisition of grants or scholarships and paid internships corroborate the maintenance of the university education course and the construction of a sense of financial autonomy in relation to the family, and the university experience means expanding the fields of possibilities that echoes in the fabric of the projects. of the future in which the desire for mobility through the transformation of financial and social conditions includes the families themselves without being characterized as an individualistic posture.